2021
DOI: 10.21123/bsj.2021.18.3.0501
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrogen and Sulfur Sprays on the Growth and Production of Broccoli Brassica Oleracea var. Italica L.

Abstract: In order to achieve optimal plant growth and production, essential nutrients must be readily available in adequate quantities and in a balanced proportion to give a good yield, especially broccoli which has health benefits that may not be found in many other plants. For this purpose, this experiment was carried out during the seasons 2019/2020 in the botanical garden of the Department of Biology, College of Science for Women, University of Baghdad, to study the effects of nitrogen and sulphur and their interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Higher results for the reproduction of cauliflower after NPK treatment (150 + 100 + 100 kg/acre) may be attributable to the increase in enzymatic metabolism in the plants followed on by NPK application, which is responsible for increasing curd size, curd weight, and yield [22]. These results were also verified with the results of Ali et al [23], Kisko et al [24] and Ashraf et al [14]. Phosphorus application in adequate quantity during the early stage of plant growth boosted the production of primordial of reproductive parts [25].…”
Section: Reproductive Parameterssupporting
confidence: 67%
“…Higher results for the reproduction of cauliflower after NPK treatment (150 + 100 + 100 kg/acre) may be attributable to the increase in enzymatic metabolism in the plants followed on by NPK application, which is responsible for increasing curd size, curd weight, and yield [22]. These results were also verified with the results of Ali et al [23], Kisko et al [24] and Ashraf et al [14]. Phosphorus application in adequate quantity during the early stage of plant growth boosted the production of primordial of reproductive parts [25].…”
Section: Reproductive Parameterssupporting
confidence: 67%
“…stem diameter (St. D mm): Table3shows that N3 caused a significant decrease in stem diameter 9.8 mm and results disagreed with results obtained by43,44 about Jatropha curcas and Broccoli. Interaction treatment SM2N3 significantly decreased St. D of rosemary plants 9.399mm.…”
mentioning
confidence: 64%
“…It was found that spraying the growth regulator cytokinin mitigates the toxicity of saline water, perhaps through vegetation growth parameters, and also reduced lipid peroxidation, improved oxidative defense in leaves, and increases membrane permeability, as well as substitutes the oxidative damage by enhancing antioxidant defense mechanisms such as increasing the enzymatic activity of superoxide, catalase, peroxidase, ascorbate peroxidase, and scavenging ROS 55,56 Cytokinins also regulate the ability of plants to absorb many nutrients from the environment, including nitrogen, phosphorous, sulfur and iron 57 , which regulates mineral balance. The nutrient status of plants regulates plant growth 58 .…”
Section: Discussionmentioning
confidence: 99%